Disclosing The Language And Character Design Of Krishnayana Story Reliefs Of Prambanan Temple For A Photographic Creation Model - et. al., Asep Deni Iskandar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is a description and analysis of the process of creating photographic works based on a traditional drawing system, and how the typical depictions of the Krishnayana story reliefs of the Prambanan temple are utilized in photographic works. This paper reveals how to draw or study characters on the Krishnayana reliefs of Prambanan temples whose depictions can be used in photographic works. The study uses qualitative research with a visual language approach to explaining the strength of the story on temple reliefs and photographic works. The development of camera technology with digital processing on computers in the field of photography continues to occur. This development facilitates humans with the sophistication of digital cameras and has an impact on the lack of innovation in photographic work. The discourse that was rolled out also focused on the technique and sophistication of the tools. The issue of content is sometimes ignored by photographers. The content in photography is related to the problem of expressing messages through images. Messages can be presented through image grammar. The grammar of images used in photography is a Western way that is considered modern. This modern way of drawing has gradually shifted the traditional way. How to draw traditions, the artifacts can be seen in the reliefs of the Krishnayana story at the Prambanan temple. In this paper, it is concluded that how to draw on the Krishnayana story reliefs already uses modern depictions, such as the background layers used in Photoshop. The traditional way of drawing on Krishnayana story reliefs can be used in photographic works.